Manajemen SDM Qur'ani dalam Bingkai Worldview Keagamaan Mediatif-Holistik Rekonstruksi Modernitas Melalui Empirisme Humaniora - Wira Syuhada; Zidni Ilman; Kisanda Midisen; MH Ainulyaqin (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study develops a Qur’anic HRM model using a meditative-holistic religious worldview approach that unites both transcendental and empirical dimensions. The novelty of this research lies in the reconstruction of empirical humanities based on Qur’anic values as an alternative paradigm that integrates spirituality, intellectuality, and rationality into HRM practices. Through a philosophical-hermeneutical approach, this study analyzes the concept of khalifah (Qur’an, Al-Baqarah: 30), the multidimensional potential of humans (Qur’an, As-Sajdah: 9), and the principle of mutuality (Qur’an, At-Tawbah: 71) to reconstruct modernity. The findings reveal that a meditative-holistic worldview can bridge transcendence and empiricism by integrating spiritual, intellectual, emotional, and social dimensions. This study contributes a Qur’anic HRM model that offers integrity-based recruitment, holistic development, performance evaluation oriented toward the common good (maslahah), and collective leadership. It contributes to modern humanities by offering a synthesis between scientific rationality and Islamic spirituality, while also providing practical guidance for contemporary organizations.